2003
DOI: 10.1385/mn:27:2:121
|View full text |Cite
|
Sign up to set email alerts
|

Stress and the Developing Hippocampus: A Double-Edged Sword?

Abstract: The mechanisms that regulate neuronal function are a sum of genetically determined programs and experience. The effect of experience on neuronal function is particularly important during development, because early-life positive and adverse experience (stress) may influence the still "plastic" nervous system long-term. Specifically, for hippocampal-mediated learning and memory processes, acute stress may enhance synaptic efficacy and overall learning ability, and conversely, chronic or severe stress has been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 103 publications
1
51
0
3
Order By: Relevance
“…The role of stress in influencing the structure and function of hippocampal neurons has been a focus of a significant body of research (McEwen, 1999;Brunson et al, 2001Brunson et al, , 2003Joels et al, 2003;Blank et al, 2004). Persistent stress may contribute to deficits in hippocampus-dependent learning and memory (Luine et al, 1994), including those found during senescence (McEwen, 1999;Yau et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The role of stress in influencing the structure and function of hippocampal neurons has been a focus of a significant body of research (McEwen, 1999;Brunson et al, 2001Brunson et al, , 2003Joels et al, 2003;Blank et al, 2004). Persistent stress may contribute to deficits in hippocampus-dependent learning and memory (Luine et al, 1994), including those found during senescence (McEwen, 1999;Yau et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the development of this circuit is characterized by a particularly prolonged trajectory, and refinement of cortical synapses and connectivity patterns continues for years into the adolescent period. Thus, although the effects of stress on adult cognitive functions such as memory are often reversible, stress that occurs early in life, though amenable to behavioral and pharmacological interventions (eg, Ivy et al, 2010;Shonkoff, 2011), can permanently alter these processes (Brunson et al, 2003). Focusing on chronic and/or severe early-life stress, long-lasting deficits, contextual fear conditioning (Guijarro et al, 2007;Kosten et al, 2007;Oomen et al, 2010) Although these tests involve elements of stress and may therefore not be free of confounders, similar defects after early-life stress are found in object recognition (Brunson et al, 2005;Aisa et al, 2007;Kosten et al, 2007;Rice et al, 2008;Ivy et al, 2010;Hulshof et al, 2011) and object location (Molet et al, 2015b).…”
Section: Cognitive Consequences Of Early-life Experience Via Disruptimentioning
confidence: 99%
“…Although it is evident that sustained stress, both in early life and adulthood, can adversely affect hippocampal structure and function (Brunson et al, 2003;Buwalda et al, 2005;Magarinos et al 1996;Mirescu and Gould, 2006;Vyas et al, 2002), the molecular underpinnings for this remain unclear. Decreased expression of the neuro-trophin brain-derived neurotrophic factor (BDNF) has been implicated in stress-induced hippocampal damage and dysfunction (Duman, 2004;Gomez-Pinilla and Vaynman, 2005).…”
Section: Introductionmentioning
confidence: 99%